1999
DOI: 10.1007/bf03035869
|View full text |Cite
|
Sign up to set email alerts
|

The Pd/ n H system: Transport processes and development of thermal instabilities

Abstract: Recent years have witnessed renewed interest in the hydrogen economy, with emphasis on the metal/hydrogen system and its application to energy conversion efforts. Two industrially important aspects are emphasized, viz. the amount of hydrogen stored and the rate at which it can be transferred (absorbed/desorbed) because they are crucial factors in the design and construction of electrochemical energy conversion devices. The March 1989 announcement of excess enthalpy generation [1], the Fleischmann-Pons effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…7a -7c. In a separate study [10], we showed that the excess heat is not produced continuously over the entire electrode volume but at isolated In accordance with the concept that one experiment leads to another we noted the following: An analysis of experimental results suggests that events occurring at the contact surface of the interphase region influence the events in the bulk, ie influence the intensity and type of the nuclear events through the interactions between the D + complexes and the Pd lattice assisted by the stress fields at the reaction sites. Consequently, by placing an operating cell in an external electric field one would expect to see effects quite different from those observed in the absence of field.…”
Section: More About Reaction Sitesmentioning
confidence: 95%
“…7a -7c. In a separate study [10], we showed that the excess heat is not produced continuously over the entire electrode volume but at isolated In accordance with the concept that one experiment leads to another we noted the following: An analysis of experimental results suggests that events occurring at the contact surface of the interphase region influence the events in the bulk, ie influence the intensity and type of the nuclear events through the interactions between the D + complexes and the Pd lattice assisted by the stress fields at the reaction sites. Consequently, by placing an operating cell in an external electric field one would expect to see effects quite different from those observed in the absence of field.…”
Section: More About Reaction Sitesmentioning
confidence: 95%
“…A system far from equilibrium tends to promote cluster formation which, in turn, produces hot spots that can be displayed by infra-red (IR) imaging of the electrode surface (Mosier-Boss and Szpak 1999). The presence of "hot spots" indicates that (i) there are regions of specific interactions involving absorbed deuterium and the Pd lattice and (ii) these interactions produce intense heat sources capable of melting palladium.…”
Section: Shape Changementioning
confidence: 99%
“…4. Heat bursts are observed that must originate near the surface because their observed size is very small [48][49][50]. Very small melted regions are also seen [51].…”
Section: Answer To Question #1mentioning
confidence: 99%